Enhancing Tahfidz Program Efficacy: A Curriculum Management Approach at Islamic Boarding School - Kohar, Ayi Abdul; Asy’ari, Hasyim (Journal of Education and Learning Innovation, 2024)
This research aims to describe and analyze the implementation of the curriculum in optimizing the tahfidz program at Al-Hikamussalafiyyah Islamic Boarding School, Sumedang. This study employs a qualitative research design with a case study approach. The research is conducted at Al-Hikamussalafiyyah Islamic Boarding School in Sumedang. Data collection techniques include observation, interviews, and documentation. Data sources for this study comprise the leadership of the boarding school, tahfidz program coordinators, the teachers' council, and one student. Analytical techniques employed in this research involve data collection, data reduction, data presentation, and concluding. Triangulation methods, both in terms of technique and source, are used to validate the data. The research findings reveal that (1) the curriculum structure for tahfidz al-Qur'an at Al-Hikamussalafiyyah Islamic Boarding School encompasses several planning stages, including setting basic and learning objectives, defining material targets and achievements, and allocating learning time, as well as organizing tasks and learning materials. (2) Curriculum implementation in optimizing the tahfidz program includes execution, with the learning process comprising three stages of initial, core, and closing activities, the application of methods tailored to each class level, and learning conditions.